Credit assess and welfare status of smallholder: evidence from farmers in Kwara state, Nigeria - Osasona, Kehinde Kikelomo (2024)
Lack of proper access to credit poses a major threat to agricultural production and food security globally, yet commercial bank, co-operative societies, microfinance banks, agricultural development programs, non- governmental organizations, government agricultural schemes offer loans to low-income individuals who have need of it despite the challenges encountered in accessing and managing it by farmers. However, there is limited research on the effectiveness of credit programs in improving the welfare of smallholder farmers in Kwara state, Nigeria. Therefore, the nexus between credit assess and welfare status of smallholder farmers in Kwara state, Nigeria was analyzed. Quantitative data was collected from 120 smallholder farmers selected through a three multi-stage sampling techniques. Data was analyzed using descriptive statistics, per capita expenditure, per capita income, and ordinary least square. Results showed that most respondents were middle-aged married males engaged primarily in farming, with moderate education, experience and income levels. It was also revealed that there is high awareness and use of credit. The major source of credit for the respondents was cooperative societies (60%) with least of agricultural development programs (3.92%). Overall, 58.93% of smallholder farmers had access to credit. Key perceived benefits were investment in agriculture (32.50%) and increased productivity (31.67%), and diversification of farming activities (20.83%). The significant factors influencing the welfare status of smallholder farmers include credit amount, age and household size. Based on these findings, it is recommended that both formal and informal sources of credit be established for farmers within the farmers’ vicinity.